Librarian Interpersonal Communication At The Digital Reading Corner In Dinas Perpustakaan dan Kearsipan Pemerintah Kab. Labuhan Batu - Hidayani Syafitri Harahap; Anang Anas Azhar; Muslih Fathurrahman (Pena Cendekia Insani, 2022)
This research was conducted at the Library and Archives Office of Labuhan Batu Regency. The purpose of this study was to find out about the Interpersonal Communication of Librarians in the Digital Reading Corner at the Library and Archives Service of the Labuhan Batu Regency Government. The research method used is a qualitative method, this research intends to reveal the phenomena that exist in the field, namely: How is the interpersonal communication of libraries to users in the digital reading corner. Next, the researchers conducted interviews with 2 librarians at the Labuhan Batu Regency Library and Archives Service. The results of the study indicate that the library is the human resource in the library which is used as a benchmark for the progress of a library or digital reading corner. A librarian is a person who provides and carries out activities in a library or digital reading corner in an effort to provide a service to users in accordance with the vision and mission of the parent institution Constraints that often occur in digital reading corners are the lack of human resources, the lack of facilities provided, the lack of interest in reading by the public. It can be concluded that the constraint of the digital reading corner with circumstances that can hinder the ease and development of the digital reading corner.